Jenis Kelamin dan Durasi Penggunaan Gadget pada Speech Delay - Idola Perdana SS idola; Endang Mei Yunalia; Kausar Afif Fatwa (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2023)
Language is a system of signs or rules used by children to communicate and adapt to their environment, with the aim of exchanging ideas, thoughts and emotions. It is not uncommon during this developmental period to find children's growth and developmental disparities, one of which is speech delay. One of the factors that influence this is the gender and the use of gadgets. This study uses correlational analysis method with an expost facto approach to 70 respondents, data collection is done by questionnaire, and accidental sampling technique. The independent variables in this study are gender and duration of gadget use for the dependent variable in this study is speech delay. Statistical analysis in this study used pearson Chi square and Spearman rank. The results of the statistical test for gender variable with speech delay using Pearson Chi square obtained a p-value of (0.001) <α, which means that there is a significant relationship between gender variable and speech delay, while for the variable duration of gadget use with speech delay Using Spearman Rank, a p-value of (0.03) <α means that there is a relationship between the variable duration of gadget use and speech delay. Based on the results of the study, it was found that there was a relationship between gender and duration of gadgets using with the incidence of speech delay.